Self-destruction of complex systems
1 online resource.
Keywords: "This book is the first to provide a general theory of self-destruction in complex systems. The volume suggests a unified theory of systemic self-destruction applicable to natural, social and cultural phenomena. The contributors work collaboratively to prove that most of the non-distributed complex systems in nature and society sooner or later experience critical development leading to unintended and irreversible self-annihilation. The chapters also show that the relations of such systems to their own distinctiveness and other systems may result in specific communicative pathologies (such as redundancy, autoimmunity, inflation and noisy signalling) which tend to reinforce each another. This book updates some popular models of systemic self-destruction-from autoimmunity and self-organized criticality to imperial overstretch-and discusses some prominent cases, from supernova explosions to the Stalinist show trials. The interdisciplinary style of narration ensures the accessibility of the materials and theories presented for the specialists and students from different fields. As such, it will appeal to those interested in complexity studies from the areas of sociology, history, immunology, computer science, literary criticism, cultural studies, political science and international relations"--